The second person in the interpretation and reinterpretation in orchestra row - Epele, Juliette (2021)
Numerous studies on temporal regulation show that music performers not only build a stable self-regulatory system, but also co-regulate their performance by interacting with other musicians and with the music they produce together. Enactivism postulates that expressive musical performance is based on the conjunction of entrainment, sensorimotor prediction and expressive alignment (Leman, 2016), from which actions with expressive intention derive. However, little is known on how expressive intentions are mutually grasped by co-partners during performance. It is assumed that the second person perspective of mental attribution (a post cognitive approach related to social cognition) that refers to the ways direct, spontaneous, explicit and reactive intentional and reciprocal expressions take place between interactants (Pérez and Gomila 2018), can provide an answer.